INVESTASI BAGI HASIL DALAM EKONOMI MIKRO ISLAM - Hendra Hendra; San Putra; Hadi Gunawan (Universitas Muhammadiyah Sumatera Utara, 2026)
Profit-sharing investment represents a cornerstone of Islamic microeconomics, embodying principles of justice, risk sharing, and ethical financial participation. This study aims to analyze the implementation, challenges, and optimization strategies of profit-loss sharing (mudharabah and musyarakah) contracts in microeconomic contexts. Employing a qualitative descriptive-analytical approach, data were collected from secondary sources, including scholarly articles, books, and institutional reports published within the last five years. The findings indicate that while profit-sharing investment has significant potential to empower micro-entrepreneurs and promote financial inclusion, its practical implementation is constrained by institutional limitations, information asymmetry, risk aversion, and regulatory ambiguity. Successful application of profit-sharing mechanisms depends on transparency, participatory monitoring, financial literacy, and supportive social and legal frameworks. The study also identifies strategic pathways to optimize profit-sharing investment, such as institutional capacity building, technological adoption, and policy interventions. Overall, profit-sharing investment can serve as an effective, inclusive, and ethically grounded tool in Islamic microeconomics, provided that both institutional and socio-cultural conditions are adequately addressed.